INSTRUMEN EVALUASI SIKAP SISWA SMP DALAM PEMBELAJARAN IPA BERBASIS DISCOVERY LEARNING MODEL - Laila Khusnah; Cici Ilma Arijanah (JURNAL BIOSHELL, 2018)
The research aims to test the validity of attitude evaluation instrument in order to measure the students’ learning attitude in line with their positive respons to science instructionalbased on Discovery Learning Model. The type of the develpment research uses Thiagarajan 4D model development research design. The attitude evaluation instruments are validated by the theoritical expert and science teacher as the practical expert before being used experimentally to class VIIAstudents of Al – Maufijunior high school Tempurejo, Jember regency. The validation results of the attitude evaluation instruments developed have 3,58 score or categoried sufficenty valid and effective used to instructional process to arise curiosity, honesty, diligent, and critical attitudes. The effectivity of the instruments is proven by the students’ positive respons score up to 90, 63%.Keywords: evaluation instrument, attitude, Discovery Learning Method.